Increasing public value: public leadership and strategic management to tackle tough problems with citizens and communities - Benington, John (Henry Stewart Talks, 2010)
Structure of argument, Profound changes in the context: Ecological, Political, Economic, Social, Technological, Organisational, Competing paradigms for public leadership and management, Three nodes of networked governance, Public value, What is public value?, What do we mean by public value, The public sphere, The creation of public value, Public value chain, The inverted pyramid of public value, The strategic triangle, Knowledge and capabilities for co-creation of public value